knowledge, perceptions and practices regarding zika virus of university students in northern Colombia (Santa Marta, 2016) - Perafán-Ledezma, Astrid Lorena; Martínez-Dueñas, William Andrés (Duazary, 2019)
This study focuses on 171 university students’ level of knowledge, perceptions and practices regarding Zika virus and its vector in Santa Marta (Colombia) in 2016. A survey was conducted and answers about causative agent and mode of transmission were classified into three levels of knowledge. 32.1% of the students stated that they had suffered from Zika. A 60% stated that they knew what the disease was, however, only 29.2% knew what the causative agent was and 45.6% knew the mode of transmission. Regarding the level of knowledge, only 14.6% knew the causative agent and the mode of transmission (Level 2). In general, the students recognize Zika’s symptoms, and 53.8% consider Zika to be very serious and more than half consider that they, the community and the government are responsible for controlling the vector. Even though more than half the students know the most important strategies as regards on how to control the vector, they do not practice them; this may be explained by the characteristics of their daily live dynamics, the lack of community organization, deficiency in the system of public health and climate change. It is recommended to implement permanent vector control strategies that consider the sociocultural characteristics of at-risk populations.